Series elastic actuation for improved transparency in time delayed haptic teleoperation. (November 2019) - Budolak, Daniel; Ben-Tzvi, Pinhas
Abstract: This paper demonstrates that incorporating passive compliance to the follower (slave) by means of a series elastic actuator (SEA) improves system transparency for haptic teleoperation applications with large time delays. Time delay induced force and position tracking errors limit the practical implementation of teleoperation systems. Traditional approaches have focused on passifying the communication channel and estimation methods to improve transparency, but performance degrades in large delays. In a force-position architecture using a Smith predictor, the ability to implement force control through position control with an SEA aids in increasing transparency of the system. The position drift common in most time delayed systems is eliminated with the proposed method while maintaining an accurate force reflection for a constant round trip time delay of two seconds. The combined actuation and sensing capabilities of the SEA also provide a means for detecting and correcting for variations in the environment contact location. This aids in estimating the follower dynamics for the predictor as both position and force information of the environment are captured. The proposed method is validated through simulation and experiment involving stiff and soft unilateral environment contact. The results of haptic teleoperation with an SEA demonstrate the effectiveness of compliance for accurate system transparency and improved performance in comparison to stiff actuation, while reducing controller complexity.